Investigating the factors that influence Chinese undergraduate students' sustained use of open source communities. - Xinyi Wang; Rafiza Abdul Razak; Siti Hajar Halili (PLoS ONE)
The progress of open source technology is inseparable from cultivating open source talents in universities. The combination of open source communities and university education can cultivate students' practical innovation abilities. Currently, we are facing problems such as the shortage of open source talents and the sustained use of open source technologies by open source talents. In addition, there are relatively few studies that explore the influencing factors of open source talents' sustained use of open source communities, and research in this area plays a key role. This study aims to analyze the factors that influence the sustained use of open source communities among Chinese university students. The study used random stratified sampling to survey 803 undergraduate students in Yunnan Province. The influencing factors in innovation diffusion theory and the technology acceptance model were analyzed using the partial least squares structural equation model. Positive and significant effects among the seven factors of relative advantage, compatibility, trialability, observability, perceived ease of use, perceived usefulness, and perceived attitude, as well as the two model interrelationships, were demonstrated. In addition, perceived attitude and perceived usefulness have a significant positive impact on students' sustained intention, and their mediating role is confirmed. In addition, the model is not affected by different students (gender, major, university, grade). This study provides valuable insights into the development of open source talent and the application of open source communities in education.